In vitro antimicrobial efficiency of a mouthwash containing triclosan/gantrez and sodium bicarbonate Eficiência antimicrobiana in vitro de um enxaguatório bucal contendo triclosan/gantrez e bicarbonato de sódio - Juliana Rico Pires; Carlos Rossa Junior; Antonio Carlos Pizzolitto (Brazilian Oral Research, 2007)
Several antiseptic substances have been used as adjuncts to routine mechanical procedures of oral hygiene, based on their antimicrobial effects. The objective of this study was to assess in vitro the antimicrobial efficiency of a mouthwash containing Triclosan/Gantrez and sodium bicarbonate in comparison to both positive and negative controls. Standard strain samples of Escherichia coli, Pseudomonas aeruginosa, Actinomyces viscosus and Bacillus subtilis were used. Samples of Streptococcus mutans and Gram-negative bacilli were collected from 20 volunteers (10 with a clinically healthy periodontium and 10 presenting biofilm-associated gingivitis). Evaluation of the antimicrobial activity was performed by determining the minimal inhibitory concentration (MIC). The results indicated that the test solution inhibited the growth of both Gram-negative and Gram-positive microorganisms from the volunteers’ saliva as well as that of the standard strains at the MIC dilution of 1:20, whereas the MIC dilution of 0.12% chlorhexidine against the same bacteria was 1:80. Thus, even though the tested mouthrinse solution presented an in-vitro antimicrobial activity superior to that of a placebo, it was inferior to that of chlorhexidine. Diversas substâncias antisépticas têm sido utilizadas como adjuntos aos procedimentos mecânicos rotineiros de higiene oral, com base em seus efeitos antimicrobianos. O objetivo deste estudo foi avaliar, in vitro, a eficiência antimicrobiana de um enxaguatório bucal contendo Triclosan/Gantrez e bicarbonato de sódio, em comparação a controles positivos e negativos. Linhagens padrão de Escherichia coli, Pseudomonas aeruginosa, Actinomyces viscosus e Bacillus subtilis foram utilizadas. Amostras de Streptococcus mutans e Bacilos Gram-negativos foram coletadas de 20 voluntários (10 com um periodonto clinicamente saudável e 10 com gengivite associada à presença de biofilme). A avaliação da atividade antimicrobiana foi realizada pela determinação da Concentração Inibitória Mínima (CIM). Os resultados mostraram que a solução teste inibiu o crescimento de microrganismos Gram-negativos e Gram-positivos da saliva dos voluntários, bem como das linhagens padrão na CIM de 1:20, enquanto que a CIM da diluição de clorexidina 0.12% contra as mesmas bactérias foi de 1:80. Desta forma, apesar de o enxaguatório bucal testado apresentar atividade antimicrobiana in vitro superior à do placebo, esta foi inferior à da Clorexidina.